A successfully treated malignant melanoma arising in a large congenital vulvar blue nevus. Issue 6 (13th July 2020) - Lin, Weizhao; Song, Pingping; Ran, Xiaoxia; Li, Ruiman; Jiang, Xuefeng
Abstract: An atypical cellular blue nevus, a benign mass, may sometimes transform into a malignant melanoma. Here, we report a rare case of melanoma arising in a large congenital vulvar blue nevus. A 28‐year‐old Chinese woman presented to our hospital with a chief complaint of a vulvar mass that had persisted for 8 years. The patient underwent extensive local excision, followed by reconstructive surgery of the female reproductive tract. The mass was diagnosed as being a vulvar malignant melanoma. Postoperatively, the patient received interferon immunotherapy and recovered without complications. No evidence of recurrence was observed after 32 months of follow‐up. Our case thus shows that comprehensive treatment with surgery supplemented by immunotherapy can be effective against a malignant melanoma arising in a vulvar blue nevus.